SCN1A Mutation—Beyond Dravet Syndrome: A Systematic Review and Narrative Synthesis - Ding, Jiangwei; Li, Xinxiao; Tian, Haiyan; Wang, Lei; Guo, Baorui; Wang, Yangyang; Li, Wenchao; Wang, Feng; Sun, Tao (Frontiers in Neurology, 2021)
Background:SCN1A is one of the most common epilepsy genes. About 80% of SCN1A gene mutations cause Dravet syndrome (DS), which is a severe and catastrophic epileptic encephalopathy. More than 1,800 mutations have been identified in SCN1A. Although it is known that SCN1A is the main cause of DS and genetic epilepsy with febrile seizures plus (GEFS+), there is a dearth of information on the other related diseases caused by mutations of SCN1A. Objective: The aim of this study is to systematically review the literature associated with SCN1A and other non-DS-related disorders. Methods: We searched PubMed and SCOPUS for all the published cases related to gene mutations of SCN1A until October 20, 2021. The results reported by each study were summarized narratively. Results: The PubMed and SCOPUS search yielded 2,889 items. A total of 453 studies published between 2005 and 2020 met the final inclusion criteria. Overall, 303 studies on DS, 93 on GEFS+, three on Doose syndrome, nine on the epilepsy of infancy with migrating focal seizures (EIMFS), six on the West syndrome, two on the Lennox–Gastaut syndrome (LGS), one on the Rett syndrome, seven on the nonsyndromic epileptic encephalopathy (NEE), 19 on hemiplegia migraine, six on autism spectrum disorder (ASD), two on nonepileptic SCN1A-related sudden deaths, and two on the arthrogryposis multiplex congenital were included. Conclusion: Aside from DS, SCN1A also causes other epileptic encephalopathies, such as GEFS+, Doose syndrome, EIMFS, West syndrome, LGS, Rett syndrome, and NEE. In addition to epilepsy, hemiplegic migraine, ASD, sudden death, and arthrogryposis multiplex congenital can also be caused by mutations of SCN1A.